Association of alcohol use disorders with amyotrophic lateral sclerosis: a Swedish national cohort study. (29th January 2015) - Ji, J.; Sundquist, J.; Sundquist, K.
Abstract : Background and purpose: Cigarette smoking is associated with amyotrophic lateral sclerosis (ALS), but the association between alcohol consumption and ALS is not clear. Our aim was to clarify this using a national cohort study design in Sweden. Methods: Individuals with alcohol use disorders (AUDs) were identified from several nationwide registers, and they were linked to the Swedish Hospital Discharge and Outpatients Registers to identify the incidence of ALS. Standardized incidence ratios (SIRs) were used to examine the risk of ALS amongst individuals with AUDs compared to those without AUDs. Results: A total of 7965 patients were diagnosed with ALS during the study period 1973–2010. The incidence of ALS amongst individuals with AUD was lower compared to individuals without AUD with an overall SIR of 0.54 (95% confidence interval 0.45–0.63). The study population was further stratified by gender, educational attainment, birth country, follow‐up period and a diagnosis of chronic obstructive pulmonary disease (as a proxy for smoking), and the observed inverse association between AUD and ALS was consistent for all the stratified analyses. Conclusions: In this follow‐up study, heavy alcohol consumption, as shown by registration for AUD, was inversely associated with the incidence of ALS. However, further studies are needed to disentangle the contribution of other potential confounding factors on the observed association. Abstract : Clickhere to view the accompanying paper in this issue.